PENERAPAN STRATEGI METAKOGNISI PADA COOPERATIVE LEARNING TIPE STAD UNTUK MELIHAT PERKEMBANGAN METAKOGNISIDAN MENINGKATKAN PRESTASI BELAJAR SISWA SMA PADA MATERI ELASTISITAS - Sucinta, Gesha Deliana (2016)
This study aims to know the development of students' metacognition and the increase of students' achievement on the elasticity concept used metacognitive strategies in cooperative learning STAD-type. Often students have difficult in solving the problem in physics subject because they don't know what they have to do, it takes learning thatcanexercisestudents'metacognition ability to solve the problem in that issue that could haveimplication for students'learning achievement. This study was conducted on one of the upper secondary school (n = 31, grade 10). The instrument for the development of metacognitive knowledge is used the knowledge questionnaires andJPS, students did it by themselves, used internet sources, discussions. The results of this study indicated that the development of students' metacognitive knowledge significantly when the discussion and also at the last meeting,it was showed by the development of students' answers who answered inappropriately and didn't accordance with the elasticity concept in answers the JPS. It is also used a questionnaires to determine the profile of students'metacognitive control and awareness and for students'metacognitive awareness were has an average 3,16 and students'metacognitive controlhas an average 3,18 are included in quite good category. To measure theincrease of students' achievement used pre and post test in a form three-tier test and obtainedthe average of normalization gain value 0,424 and it showed the increase in students' achievement is in a medium category. Based on the analysis of these data indicated that with apllyingmetacognitivestrategies in cooperative learning STAD-type, the development of students' metacognitionis quite good and increasingstudents' learning achievement.